Relationship between peer attachment and adolescent positive well-being with gender as the moderating factor in Malaysia - Rajendran, Kogilavani; Karuppannan, Gunasegaran; Binti Juhari, Rumaya; Kadir, Asnia; Jamba, Rosnah (Revistia, 2023)
Identifying protective factors that could influence the positive well-being of adolescents is important as positive development view emphasizes the possibility of adolescents developing positive traits based on their strengths, positive qualities, and supportive environments. This study examines the relationship between peer attachment with positive adolescent well-being and the role of gender as a moderator for links between peer attachment with positive adolescent well-being. A total of 400 7th Grade students from government schools in the Federal Territory of Kuala Lumpur and state of Selangor were involved in this study. Adolescent positive well-being and peer attachment were measured using the Positive Youth Development Scale and Inventory of Peer and Parent Attachment. The results show that peer attachment was  predictor of adolescent positive well-being. The study also found that gender moderated the relationship between peer attachment and adolescent positive well-being. This study provides information on factors that can help the positive development of adolescents. Identifying these factors will provide insight on events or experiences that will increase the occurrence of positive outcomes and reduce the likelihood of negative outcomes.